Hybrid On-Premise to Cloud Data Migration: Architectural Patterns for Controlled One- Way Synchronization (International Journal of Engineering & Extended Technologies Research (IJEETR), 2024)
Hybrid data migration strategies have become essential as enterprises transition from legacy on-premise systems to modern cloud platforms. While full bidirectional synchronization can provide flexibility, many organizations require controlled one-way data synchronization to ensure data governance, regulatory compliance, and system stability during phased modernization initiatives. This article examines architectural patterns for implementing hybrid on-premise to cloud data migration with controlled one-way synchronization, enabling enterprises to move operational or analytical workloads to the cloud while maintaining the integrity of existing systems. The study discusses migration drivers, including scalability, performance optimization, and cost efficiency, along with challenges such as data consistency, latency management, and operational risk. It presents commonly adopted architectural approaches including batch replication models, event-driven streaming pipelines, change data capture (CDC) frameworks, and staging-layer mediated synchronization. The article also outlines governance mechanisms required to enforce strict one-directional data flows, preventing unintended data modification in legacy environments. Furthermore, the paper evaluates enabling technologies such as distributed messaging systems, data integration platforms, and cloud-native data services that support hybrid migration architectures. Through conceptual diagrams, tables, and analytical comparisons, the article demonstrates how organizations can implement scalable and resilient pipelines while maintaining controlled synchronization boundaries. The proposed architectural patterns provide a structured approach for enterprises planning incremental modernization initiatives, enabling them to leverage cloud analytics, artificial intelligence, and large-scale storage capabilities without disrupting critical on-premise operational systems. Overall, the presented framework highlights best practices for designing secure, governed, and efficient hybrid migration pipelines that support enterprise digital transformation while minimizing operational risk.
Keywords: Hybrid Data Migration; Cloud Migration Architecture; One-Way Data Synchronization; Change Data Capture (CDC); Hybrid Cloud Integration; Data Replication Frameworks; Event-Driven Data Pipelines; Enterprise Data Modernization; Data Governance; Distributed Data Architecture